Parental Knowledge and Perception Towards the Use of Conscious Sedation (Nigerian Dental Journal, 2026)
Background: Behavioural management alleviates dental anxiety and instils a positive dental attitude. Conscious Sedation is a pharmacological behavioural management where medications are administered to achieve a minimally depressed consciousness where patient can independently maintain their air way and verbal contact maintained.Aim: To assess parental knowledge and perception towards the use of conscious sedation in dental management of children.Methods: This was a descriptive cross-sectional study on 150 parents of children that presented at the Paediatric Dental Clinic of LUTH. Questionnaires on knowledge and perception of conscious sedation were administered to parents. SPSS version 25 was used for data analysis. Numeric variables were presented using mean and standard deviation. Frequency and percentages were presented for categorical variables. The significance level was set at p≤ 0.05Results: 150 parents with a mean age of 38.13±8.37years. More than half of the participants (56.7%) had not heard of conscious sedation prior to this study. Out of the 65 participants who had heard of conscious sedation, 38(58%) of them had a good knowledge on conscious sedation while 67.4% had a positive perception of conscious sedation.  However, a total of 112 (75%) of the 150 participants had a poor knowledge of conscious sedation.Conclusion: Majority of the study participants had a poor knowledge of conscious sedation. However, most of the parents who had heard of conscious sedation prior to the study had good knowledge and good perception of conscious sedation.
Keywords: Paediatric conscious sedation, parental perception, parental knowledge